The Correlations between Postmortem Brain Pathologies and Cognitive Dysfunction in Aging and Alzheimer's Disease - Qiu, Wen-Ying; Yang, Qian; Zhang, Wanying; Wang, Naili; Zhang, Di; Huang, Yue; Ma, Chao (Current Alzheimer Research, 2018)
Background: The pathological diagnostic criteria for Alzheimer's disease (AD) updated by the National Institute on Aging-Alzheimer's Association (NIA-AA) in 2012 has been widely adopted, but the clinicopathological relevance remained obscure in Chinese population. Objective: This study aims to investigate the correlations between the antemortem clinical cognitive performances and the postmortem neuropathological changes in the aging and AD brains collected in a human brain bank in China. Method: A total of 52 human brains with antemortem cognitive status information [Everyday Cognition (ECog)] were collected through the willed donation program by CAMS/PUMC Human Brain Bank. Pathological changes were evaluated with the “ABC” score following the guidelines of NIA-AA. The clinicopathological relationship was analyzed with correlation analysis and general linear multivariate model. Results: The general ABC score has a significant correlation with global ECog score (r=0.37, p=0.014) and most of ECog domains. The CERAD score of neuritic plaques (C score) has a significant correlation with global ECog score (r=0.40, p=0.007) and the majority of ECog domains, such as memory (r=0.50, p=0.001), language (r=0.45, p=0.002), visuospatial functions (r=0.31, p=0.040), planning (r=0.35, p=0.021) and organization (r=0.39, p=0.010). The Braak stage of neurofibrillary tangles (NFTs) (B score) has a moderate correlation with memory (r=0.32, p=0.035). The Thal phases of amyloid-β (Aβ) deposits (A score) present no significant correlation with any of ECog domains. Conclusion: In this study, we verified the correlation of postmortem C and B scores, but not the A score with cognition performance in a collection of samples from the Chinese human brain bank.
Keywords: cognitive function